Drug Recording and Classification by the WHO Research Centre for International Monitoring of Adverse Reactions to Drugs - Helling, Margaretha; Venulet, J. (Methods of Information in Medicine, 1974)
Recording and classifying drugs reported in relation to suspected drug adverse reactions by fifteen countries has required the development of a special system. A comprehensive cross reference system between different types of drug names (INN, other nonproprietary names, trade names, etc.) and their occurrence in single and multiple ingredient products has been developed. Separate pharmacologic and therapeutic classifications designed for the needs of drug monitoring provide for farther special grouping.On the basis of accumulated data, some analysis is given of reporting patterns and drug profiles in different countries.
Keywords: Drug Recording System; Drug Classifications; WHO Drug Monitoring Centre; International Drug Profile